Cannabis health survey on usage in women with spinal cord injury and knowledge among physicians: A cross-sectional study. (4th March 2023) - Lee, Amanda H.X.; Tse, Emmanuel K.; Nightingale, Thomas E.; Sachdeva, Rahul; Walter, Matthias; Krassioukov, Andrei V.
Abstract : Objective: Individuals with spinal cord injury (SCI) report using cannabis to self-manage chronic pain and spasticity. However, its safety and efficacy are not well understood. As more women with SCI are pursuing motherhood, clinicians must consider the possibility of maternal cannabis use and its impact on fetal development. Moreover, due to the lack of current evidence for cannabis, it is important to characterize the perceptions and knowledge of physicians towards both recreational and synthetic cannabinoids. Design: Two anonymous surveys (10-items each) were conducted. Setting and Participants: Women with SCI ( n = 20) completed an anonymous, online survey regarding cannabis use. Physicians at a Canadian SCI rehabilitation center ( n = 15) completed a survey on their knowledge of recreational and synthetic cannabinoids among individuals with SCI. Outcome measures: Survey 1 evaluated cannabis use patterns and perceptions before/after SCI in women, including during pregnancy and breastfeeding. The aim of Survey 2 was to understand the perception and current knowledge of physicians regarding recreational cannabis and synthetic cannabinoid use by patients with SCI. Results: At the time of survey, 7 women with SCI reported use of cannabis, only 4 of them used prior to injury. Managing tone/spasticity ( n = 5) was the major reported benefit of cannabis use. Women used cannabis during pregnancy and/or breastfeeding as a sleep aid or relief for morning sickness ( n = 1 pregnancy, n = 1 breastfeeding, n = 1 both). The most-reported challenge with cannabis use was difficulty obtaining consistent, desirable effects ( n = 5). Almost all physicians ( n = 13) described their knowledge on recreational cannabis products as "none, very little or poor", with greater overall comfort and knowledge of synthetic cannabinoids. Conclusion: Due to the reported use of cannabis during pregnancy/breastfeeding and current impoverishment of physicians' knowledge (particularly regarding recreational cannabis products), it is imperative to further investigate the safety and efficacy of cannabis use in women with SCI.